Wood stove combustion modeling and simulation: Technical review and recommendations. (October 2021) - Koraïem, Mahmoud; Assanis, Dimitris
Abstract: With the rise in wood stove use in recent years, a number of experimental research efforts have been undertaken with the objective of developing cleaner, and more efficient stove designs. However, numerical modeling of stoves is still in its nascent years, thus making it imperative to start adapting more mature computational techniques, established in other combustion-based applications (e.g., combustion engines), to wood stoves. This study focuses on a critical review of the state-of-the-art in wood combustion modeling techniques and on providing recommendations for needed enhancements. In order to develop an optimum conceptual numerical model for wood stoves, the basic processes inside the stove are broken down and isolated into generic computational processes: surface reactions, gas reactions, and the fluid flow. Then state-of-the-art numerical efforts for wood stove and similar applications are broken down in a similar manner to highlight points of strength and possible improvements. Finally, based on the comparison between the different models, an improved modeling approach is proposed as a road map for future research efforts to achieve a higher fidelity wood stove numerical model.